Strengthening the Legitimacy of the Indonesian Constitutional Court Decision through Supermajority Requirement: Lesson from the South Korean Experience - Sulistyowati, Tri; Satrio, Abdurrachman (Revista de Investigações Constitucionais, 2023)
Criticism toward the legitimacy of the constitutional court decisions in judicial review cases remains to be a common problem for many courts around the world, including the Indonesian Constitutional Court (popularly known as ’MK’). Thus, the Indonesian Constitutional Court was established with its structure designed to minimize the legitimacy problems in its decisions. Although efforts to minimize the problem of legitimacy have been made, the criticism toward Indonesian Constitutional Court’s legitimacy remains throughout its development, especially when the institution decides against public opinion. Over the years, the issue of legitimacy became even more complicated; the existing political institutions had expressed their intent to intervene in the Indonesian Constitutional Court through their power to appoint its judges. As such, there is a strong likelihood that the public will not consider the Court Decisions as independent, which in turn may further hamper its legitimacy. To resolve this issue, this paper shall discuss the ’supermajority’ mechanism, in which a supermajority vote amongst the judges is required in order for a law to be declared unconstitutional. We use Constitutional Court of Korea’s experience in implementing this mechanism as an example to prove that the adoption of the supermajority requirement has the potential to succeed in strengthening the legitimacy of the decisions of the constitutional courts as well as making it more difficult for the political institutions to capture the court.